Targeting as an enabling factor in NATO military operations - Bueno Fernández, Alejandro (Journal of the Spanish Institute for Strategic Studies, 2021)
The conflicts of this new century are influenced by the complexity of the global socio-political scenario, rapid technological and doctrinal development or necessary compliance with international law. This changing scenario, among many other factors, greatly influences the planning of a military operation. Understanding the course of the last century’s history provides a historical context that explains the reason –and the need– for NATO’s 2010 organisational model; as well as the creation of the concept of targeting and its subsequent integration into the Alliance’s organisational structure. This paper reviews targeting from a holistic perspective –doctrinal, legal and military innovation– in order to determine whether this concept fulfils an enabling role within NATO’s military operation planning process.